Socrates’ Accusers - Kelessidou, Anna (Peitho. Examina Antiqua, 2011)
We have unfortunately very little information on the three accusers of Socrates: Meletus, Anytus, and Lycon. Notwithstanding this, the present paper attempts to discuss the circumstances and motives that led to Socrates’ trial. Furthermore, the article deals with Socrates’ crucial stand after the verdict and considers the philosopher’s arguments as these have been presented in the first tetralogy.